2013
DOI: 10.1002/pits.21683
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Multifocused Prevention Program on Preschool Children's Competencies and Behavior Problems

Abstract: This study was designed to assess the effectiveness of a multifocused (child‐, teacher‐ and parent‐focused) prevention program for Romanian preschoolers, targeting social–emotional competence development, as well as reduction of behavior problems. Fourteen classrooms were randomly assigned to the intervention and control conditions. Subsequent hierarchical linear analyses indicated that intervention‐group children performed better on experimental tasks measuring emotion knowledge and social problem‐solving str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 56 publications
1
20
0
4
Order By: Relevance
“…A study of Romanian children participating in interventions to develop their social and emotional competence found them to be more successful in social problem solving (Ştefan & Miclea, 2013). Studies examining the IY Child Training Program have also observed improvements in the social problem-solving skills of children among whom the program is applied (Webster-Stratton et al, 2001b, 2011, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…A study of Romanian children participating in interventions to develop their social and emotional competence found them to be more successful in social problem solving (Ştefan & Miclea, 2013). Studies examining the IY Child Training Program have also observed improvements in the social problem-solving skills of children among whom the program is applied (Webster-Stratton et al, 2001b, 2011, 2013.…”
Section: Discussionmentioning
confidence: 99%
“…Del mismo modo, las mejoras reflejadas en el grupo experimental tras la intervención, concuerdan con los resultados hallados recientemente en otros estudios que también evaluaron comportamientos prosociales entre la población infantil (Moraru et al, 2011;Ştefan y Miclea, 2013). Concretamente, el programa PATHS Preschool llevado a cabo con alumnado de 3 años, produjo efectos positivos en variables como la cooperación y la independencia social después de un año de intervención, aunque en este caso los participantes procedían de un entorno socio-económico bajo (Domitrovich et al, 2007).…”
Section: Discussionunclassified
“…En este sentido, Romer, Ravitch, Tom, Merrell y Wesley (2011) hallaron diferencias claras a favor de las niñas (8-10 años) en cuanto a comportamientos empáticos, autorregulación y competencia social. No obstante, estudios similares al presentado aquí, llevados a cabo con sujetos de la misma edad, no encontraron diferencias de género entre los niños y las niñas en competencia social (Moraru et al, 2011;Ştefan y Miclea, 2013).…”
Section: Discussionunclassified
See 2 more Smart Citations